The Impact of Food Habits on Emotional Well-Being and Sleep Patterns: An Empirical Study among Indian Youth (Journal of Informatics Education and Research, 2025)
This study examines how food habits influence emotional well-being and sleep patterns among Indian young adults. Using a structured questionnaire administered to 283 respondents, we measured dietary practices (tea/coffee consumption, vegetarianism, spice frequency, and junk-food frequency), sleep characteristics (hours, subjective sleep deprivation, dream frequency), and psychological outcomes (concentration, memory, restlessness, irritability, and temper loss). Analyses included descriptive statistics, independent-samples t-tests, one-way ANOVA, ordinary least squares regression, and exploratory factor analysis with varimax rotation. Results show that regular tea/coffee consumption is associated with increased subjective sleep deprivation, and sleep duration exhibits significant differences in concentration and irritability — participants reporting 7–8 hours of sleep show higher concentration and lower irritability than those with shorter or longer sleep durations. Regression models indicate that sleep deprivation negatively predicts concentration, while concentration and sleep duration positively predict memory performance. PCA with varimax rotation suggests three latent dimensions: Cognitive Performance, Emotional Dysregulation, and Sleep-Dream Patterns. The findings align with recent literature emphasising the mental health burden of poor dietary patterns and the complex relationship between sleep and cognition in contemporary populations. Implications include evidence-based recommendations for campus health promotion, dietary education, and sleep hygiene interventions tailored to Indian contexts. Limitations, including cross-sectional design and self-report measures, are discussed along with directions for longitudinal and mixed-methods research.